Sodium caseinate as a strategy for remote equine semen cryopreservation - Santos, Wallyson Rafael Machado; Júnior, Geraldo Francisco dos Santos; Laskoski, Luciane Maria; Celeghini, Eneiva Carla Carvalho; Kozicki, Luiz Ernandes; Vaz, Eduarda Stankiwich; Emerick, Lucas Luz; Lara, Natalia Santana Siqueira de; Silvestre, Mayara; Souza, Fernando Andrade (Archives of Veterinary Science, 2024)
The objective of this study was to determine whether the addition of sodium caseinate in different concentrations to the freezing extender medium favors sperm viability after a long period of refrigeration. For this, three concentrations of sodium caseinate were used, 0, 1 and 2%, in the cryopreservation medium, and the ejaculates were divided into nine groups 0H/0%, 0H/1%, 0H/2%, 12H/0%, 12H/1%, 12H/2%, 24H/0%, 24H/1% and 24H/2%. The stallions underwent reproductive evaluation, being included only those with sperm motility ≥ 70%. Fluorescent probes, hypoosmotic (HOST) and thermoresistance (TTR) tests were used to evaluate the functionality of the plasma membrane and the longevity of sperm cells, respectively. There was no difference (p>0.05) between groups for membrane integrity. However, for the TTR, it was possible to observe a difference (p<0.05) for the 24H/2% group, with a lower response. The integrity of the plasma membrane, compared to the refrigeration time and the concentration of sodium caseinate, did not change. Therefore, it was concluded that sperm longevity was impaired with the use of a 2% concentration of sodium caseinate, and its use is not recommended for sending refrigerated semen, for insemination or freezing, that exceeds 12 hours.